Persepsi Mahasiswa Akuntansi Mengenai Karakteristik Individu Pada Kecurangan Laporan Keuangan - Putu Riesty Masdiantini; Sunitha Devi; Gst. Ayu Ketut Rencana Sari Dewi (Universitas Pendidikan Ganesha, 2022)
The purpose of this study was to obtain empirical evidence regarding the perceptions of accounting students regarding individual characteristics of financial statement fraud. This research is a quantitative research using a quasi-experimental approach, namely the 2X2 factorial design. The number of samples in this study were 110 Undiksha Accounting S1 students who were selected through the Purposive Sampling technique. The data analysis technique used is Two-Ways Analysis of Variance (ANOVA). The results showed that the bystander effect had no effect on the occurrence of financial statement fraud. Meanwhile, whistleblowing has a significant negative effect on the occurrence of fraudulent financial statements. Meanwhile, locus of control can moderate the bystander effect relationship on financial statement fraud. However, the locus of control has not been able to moderate the relationship between the whistleblowing on fraudulent financial statements. The gender variable can moderate the bystander effect relationship on financial statement fraud. However, the gender variable has not been able to moderate the whistleblowing relationship on financial statement fraud Keywords: Fraudulent Financial Statements, individual characteristics